Upregulation of anti-human ribosomal protein S6-p240, topoisomerase II ά, cyclin D1, Bcl-2 and anti-corneal antibodies in acute psoriasis - Howard William R.; Abreu Velez Ana Maria; Howard Michael S. (Our Dermatology Online, 2011)
Background. The immunopathogenesis of psoriasis is complex, and involves alterations in the innate immunologic system Case Report: A 57-year-old female was evaluated for the presence of rapidly appearing plaques on the knees and elbows. Methods: Skin biopsies for hematoxylin and eosin examination, as well as for direct immunofluorescence and immunohistochemistry analysis were performed. Results: H&E examination demonstrated classic features of psoriasis. Direct immunofluorescence revealed positive anti-corneal antibodies with several immunoglobulins, as well as positivity to upper and deep small dermal blood vessels. Immunohistochemistry revealed an increased expression of survivin, anti-human-ribosomal protein S6-p240, Topoisomerase II ά, cyclin D1, and Bcl-2 in lesional plaques. Conclusions: The pathobiology of psoriasis seems to involve a series of molecules involved in a complex interaction between the inflammation itself, cell cycle regulation, and ectopic expression of selected molecules.